Improvement of Polylactide Properties Through Cellulose Nanocrystals Embedded in Poly(Vinyl Alcohol) Electrospun Nanofibers - Romero-Figueroa, J; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Garrido-Ayala, L; Alvarado-Almonacid, N (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
Electrospun nanofibers of poly (vinyl alcohol) (PV) were obtained to improve dispersion of cellulose nanocrystals (CNC) within hydrophobic biopolymeric matrices, such as poly(lactic acid) (PLA). Electrospun nanofibers (PV/CNC)n were successfully obtained with a final concentration of 23% (w/w) of CNC. Morphological, structural and thermal properties of developed CNC and electrospun nanofibers were characterized. X-ray diffraction and thermal analysis revealed that the crystallinity of PV was reduced by the electrospinning process, and the incorporation of CNC increased the thermal stability of biodegradable nanofibers. Interactions between CNC and PV polymer also enhanced the thermal stability of CNC and improved the dispersion of CNC within the PLA matrix. PLA materials with CNC lyophilized were also casted in order to compare the properties with materials based on CNC containing nanofibers. Nanofibers and CNC were incorporated into PLA at three concentrations: 0.5%, 1% and 3% (CNC respect to polymer weight) and nanocomposites were fully characterized. Overall, nanofibers containing CNC positively modified the physical properties of PLA materials, such as the crystallinity degree of PLA which was greatly enhanced. Specifically, materials with 1% nanofiber 1PLA(PV/CNC)n presented highest improvements related to mechanical and barrier properties; elongation at break was enhanced almost four times and the permeation of oxygen was reduced by approximately 30%. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.